Literary Modernism, Bioscience, and Community in Early 20th Century Britain - Gordon, C. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2007)
This book examines the relationship between the literary and bioscientific cultures of the period as a means of exploring the ways in which the comprehension and representation of the human body fundamentally shapes a variety of the period's communal and national visions.